Urgensi Penguatan Independensi Auditor dalam Menghasilkan Laporan Keuangan Entitas Bisnis Yang Kredibel dan Akuntabel - Syahriana Syahriana; Nailah Airin Nur Fadillah; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Auditor independence plays a crucial role in ensuring the quality and credibility of business entities’ financial statements. Numerous financial scandals have demonstrated that weak auditor independence can reduce the reliability of financial reporting and undermine public trust in the auditing profession. This study aims to analyze the urgency of strengthening auditor independence in producing credible and accountable financial statements. The research employs a descriptive qualitative approach through a literature review of auditing standards, professional regulations, and findings from previous studies. The results indicate that auditor independence is influenced by economic relationships with clients, audit tenure, managerial pressure, and the effectiveness of professional oversight. Strengthening auditor independence through restrictions on non-audit services, auditor rotation, the enhanced role of audit committees, and the enforcement of professional codes of ethics is shown to contribute to improved audit quality. This study affirms that auditor independence is a strategic element in supporting transparency, accountability, and the sustainability of business entities amid the growing complexity of the modern business environment